7(7x-7)=-196

Simple and best practice solution for 7(7x-7)=-196 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(7x-7)=-196 equation:


Simplifying
7(7x + -7) = -196

Reorder the terms:
7(-7 + 7x) = -196
(-7 * 7 + 7x * 7) = -196
(-49 + 49x) = -196

Solving
-49 + 49x = -196

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + 49x = -196 + 49

Combine like terms: -49 + 49 = 0
0 + 49x = -196 + 49
49x = -196 + 49

Combine like terms: -196 + 49 = -147
49x = -147

Divide each side by '49'.
x = -3

Simplifying
x = -3

See similar equations:

| 180-(5x-10)=8x-5 | | z-9z=4z-5-z | | 36-(3c+4)=2 | | 5(2z+6)=-4(-5-2z)+32 | | 3y+0x=18 | | 6e-2=15e+1 | | 8x+830=1250 | | -9y-6y+1y= | | A*A+B*B=C*C | | 0.07(5t-5)=0.35(t+1)-0.70 | | 47+3x=2x+37 | | x-9z=4z-5-2 | | .5x+(x-46)+(x-35)+x=360 | | 120=2x+40 | | 5x+(x-46)+(x-35)+x=360 | | 14+2z=20+1.50z | | -2b+6= | | 1/4(3a-8)= | | -7-8=9x+5-8x | | 4=4(x-4)+1-3x | | 4(x+5)(x-3)=40 | | RS=2x-8 | | 4(x+5)-(x-3)=40 | | 1m-50=10m+2 | | 3.5-2=1.5 | | 2c+13=4c | | x^3-4x^2+2x=-2 | | 7r^2+24-8=8 | | 9z-8=3 | | 2x+3(4x-10)=96 | | (3x+8)+(5x+12)=180 | | 1-15x=x+36 |

Equations solver categories